Radical Improvements to the Fourth Year Medical Student Experience Whilst on Placement at Black Country Healthcare NHS Foundation Trust - Joanna Pegg; Amar Hujan; Thomas Lowde; Annabel Ariyathurai; Devika Patel (BJPsych Open, 2025)
Aims: Feedback was collected from students at Black Country Healthcare Foundation Trust to survey their satisfaction with their psychiatry placement which has been changed from nine weeks to five and had moved away from a carousel system to allow independent learning for students. Primary aim was to assess student satisfaction with secondary aims to improve access to a broader knowledge of sub-specialities.